Synthesis of Natural Ni/Zeolite Activated by Acid as Catalyst for Synthesis Biodiesel from Ketapang Seeds Oil - Dimas Gilang Ramadhani; Alfiyan Wahyudianto Sarjono; Heri Setyoko; Nur Fitri Fatimah; Nanik Dwi Nurhayati (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2017)
The purpose of this research are to know the effect of addition Ni on the acidity value of Ni/zeolite catalyst and to know the best combination nickel and Zeolit activated by acid as a catalyst ofthe cracking process during synthesis biodiesel from ketapang seed oil. The Ni/Zeolite catalysts were prepared by immersing the zeolite activated by HCl 4 M into Ni(NO3)2 solution with concentration variation of0%, 5%, and 10%. The catalysts were characterized using XRD, SEM and FTIR. The results showed that the more Ni the more acidity value of the catalyst. The best quality of biodiesel was synthesized using combination catalysts of 5% Ni/Zeolite activated by acid.